Investigating the sociological use of slang from a hearer-oriented perspective - Masrizal Mahmud; Muhammad Sadli; Diana Fauzia Sari (Studies in English Language and Education, 2022)
Numerous studies have investigated the importance of slang in linguistics in various media, including novels. The dominant works on this subject have focused solely on the structural explanation of slang, leaving out its sociological context and meaning. Given the nature of slang itself as a pure informal language, studies about the semantic meaning of slang must be essential. This research looked into the slang words and expressions in a true-crime novel entitled ‘Black Mass’ by Dick Lehr and Gerard O’Neill in 2000. The goal is to discover the semantic meaning of slang words and expressions in the novel using the qualitative method and Mattiello’s hearer-oriented (2008) theory as the underlying theory. We applied the documentary method to retrieve the data and further analyzed it using Miles et al.  (2014) theory. Heavily influenced by the setting of South Boston and its crimes, Black Mass data indicated that this novel’s slang is primarily attributed to freshness and novelty. Subsequently, we found evidence of the novel’s use of desire to impress and faddishness, playfulness and humor, and impertinence properties. Color and musicality are this novel’s least common categories of slang, with only four occurrences in the entire manuscript. Given that the novel’s literature cover is still scarce, it is hoped that these findings are helpful to those who are interested in studying and researching the semantic area.